Re-enchanting the world - Szymański, Wojciech 1985-; Warsza, Joanna 1976- (Archive Books, 2022)
"Re-enchanting the World is a publication accompanying Małgorzata Mirga-Tas’s exhibition of the same name, shown in the Polish pavilion at the 59th Venice Biennale. The exhibit is Mirga-Tas’s manifesto on Roma identity and art, drawing inspiration from the Renaissance frescoes of the Palazzo Schifanoia in Ferrara and thus attempting to expand the European iconosphere and history of art with representations of Roma culture.The title of the project and this book is inspired by Silvia Federici’s book Re-enchanting the World: Feminism and the Politics of the Commons (2018), in which re-enchanting – a non-violent process in which women play an important role – reverses the unfortunate fate of the world, shaking off its evil spell. This publication presents Mirga-Tas’s re-enchanting of the world as a way of recovering the idea of the Roma community, with consideration to transnationality, cyclicity and the evolution of meanings, proposing a new narrative about the continuous cultural migration of images and mutual influences between Roma, Polish and European cultures.Within the multidirectional texts featuring poetry, prose and essays, as well as images of Mirga-Tas’s project and its process, we witness her re-enchantment of the world through a re-examination of identity, a recognition of feminine power, and a re-presentation of historical and contemporary visual narratives."--